The Implementation of Principalship’s Intructional Supervision (Comparative Study on Elemntery School of Inpres BTN IKIP 1 and Elementery School of Inpres BTN IKIP 2) - Andi Wahed; Sitti Habibah (Universitas Negeri Makassar, 2020)
This Research was aimed to determine the Implementation of Principalship’s Instructional Supervision on SD Inpres BTN IKIP 1 and SD Inpres BTN IKIP 2 of Makassar city which has implemented Kurtilas (Curriculum 2013). This research background is there policy regulated in implementation curriculum 2013 on which effect to instructional action so then it’s needed role principalship as instructional supervision. An approach used in this research is qualitative method, to describe comparation of both elementary schools. Data collection technique used interview, observation, and documentation technique. Data source derive some informant, activity and document which about instructional supervision activity principalship on SD Inpres BTN IKIP 1 and SD Inpres BTN IKIP 2. The result this research is implementation of instructional supervision based Kurtilas on SD Inpres BTN IKIP 1 Makassar is done by principalship trough some approach and technique that are indirect used individual and group techniques, motivating teachers contextually to continuous improvement them and used model teachers to knowledge transfer to other teachers. While the implementation of instructional supervision based Kurtilas on SD Inpres BTN IKIP 2 Makassar is done by principalship trough some approach and technique that is directly individual and group techniques, teachers’ supervision contextually on visiting class and meeting periodically. The implementation of instructional supervision based Kurtilas on SD Inpres BTN IKIP 1 is done carry out informally (individually) in a relaxed (humanist) style as well as group discussion and teacher empowerment activities as models, while the implementation of supervision based Kurtilas at SD Inpres BTN IKIP 2 is done formally in periodic group discussion activities which are also accompanied by class visits.